Review of chemicals used in nail salons (Albany, 2016)
"The review focused on the types of chemicals found in nail products, the potential adverse health effects associated with exposure to nail-product chemicals, evidence of chemical exposures in nail salon workers, and evidence supporting actions to reduce chemical exposures in nail salons. Many different types of products are used when providing nail specialty services. These products contain a large variety of chemical ingredients. Many nail-product ingredient s evaporate easily producing vapors and odors that may be inhaled or contact eyes and mucus membranes of nail salon workers and clients. Also, certain procedures during nail care generate dust which may be inhaled. Skin contact is also inherent in the use of nail-care products. Some types of chemicals commonly found in nail salon products are known to be associated with adverse health effects at relatively high exposure levels. Hence, concern has been raised about whether nail salon workers and clients could be at risk for such adverse health effects. The scope of this review is focused on summarizing existing information on the types of chemical ingredients found in nail salon products and in the nail salon indoor environment, the potential hazards of c hemicals in nail salon products , and the effectiveness of interventions to reduce potential hazards. ..."